أخلاقیات مهنة المکتبات والمعلومات: برنامج تدریبی مقترح لرؤیة طلاب قسم المکتبات والمعلومات فی ضوء میثاق أخلاقیات المهنة للاتحاد العربی للمکتبات والمعلومات (اعلم) - د. محمد فتحی محمود الجلاب (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims at introduce the Code of Ethics issued by the ArabFederation for Libraries and Information, and the definition of the four elementsthat make up the code of ethics, and raise students' efficiency in libraries andinformation section, check the effectiveness of the proposed training program tosee the students of Library and Information Department in the light of the Code ofEthics of the Union Arab libraries and information (ALLAM), and this study wasconducted on a number (35) students as a control sample, and the number of 37student as a Experimental group To find out their views with regard to the presentCode, the researcher used two approaches : experimental approach and themethodology of content analysis. the results of the study indicated there werestatistically significant differences between mean scores of differences instudents the experimental and control groups in the post application of the testand all of its components for the experimental group students, also show astatistically significant difference between the mean scores of the experimentalgroup students before and after the application of the program on all elements ofthe code of ethics of the profession supports of the dimensional application, andthere appeared a great impact of the proposed program in the concepts of theCode of the ethics of the profession. the study also found a set ofrecommendations including: the need to provide a course or curriculum forstudents in libraries and information departments in universities even studentsare able to become recognition with the ethics of the profession, and benefit of the content of the training program prepared by the researcher at the students'code of ethics in all libraries and information departments